On the noodle road : from Beijing to Rome, with love and pasta - Lin-Liu, Jen (Riverhead Books, a member of Penguin Group (USA) Inc., 2013)
A food writer travels the Silk Road, immersing herself in a moveable feast of foods and cultures and discovering some surprising truths about commitment, independence, and love.